Tunable Circularly Polarized Luminescence from Single Crystal and Powder of the Simplest Tetraphenylethylene Helicate - Hu, Ming; Ye, Feng-Ying; Du, Cong; Wang, Weizhou; Zhou, Ting-Ting; Gao, Miao-Li; Liu, Minghua; Zheng, Yan-Song (ACS nano, 2021)
Tetraphenylethylene and its derivatives are a class of aggregation-induced emission (AIE) compounds that are most extensively and successfully studied. It has been found that the simplest TPE is easy to crystallize into homochiral M crystals or P crystals. However, no research on circularly polarized luminescence (CPL) of TPE solid is documented. In this paper, we report that TPE can grow into big and nonefflorescent single crystals in single helical conformation and has large birefringence that is comparative with commercially available products. The TPE single crystals can emit strong CPL with a very high g lum value up to 0.53. Moreover, the sense and magnitude of CPL signals can be willfully tuned by simple rotation of the single crystal due to anisotropy of the crystals. This simple and promising CPL photonic material integrates emission, chirality, and birefringence together in one single crystal without needing an additional chiral dopant or conjugate polymer that can produce linearly polarized light. After being ground into fine powder and pressed as KBr pellets, the obtained nanocrystals of TPE also emit strong CPL light. Exceptionally, by mixing other achiral luminescent dyes together with TPE powder in KBr pellets, induced CPL signals were obtained, which could give full-color CPL emission. Although there were no interactions between TPE and the dyes in the pellets, induced CPL signals were realized through radiative energy transfer, providing a very simple method for the tuning of CPL emission.